2019
DOI: 10.18488/journal.107.2019.71.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Firm Size on Firms Performance in Nigeria: A Comparative Study of Selected Firms in the Building Industry in Nigeria

Abstract: The study examined the impact of firm size on firm's performance in Nigeria: A comparative study of selected firms in the building industry in Nigeria using annual data from 2004 to 2017. The technique used in the research work was panel analysis. Based on the financial measurement of performance using both return on assets (ROA) and return on equity (ROE), two out of the four variables used as an indicators of size were statistically significant in determine return on assets which are total sales and age of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 6 publications
2
20
0
1
Order By: Relevance
“…Besides that, an increase in a firm's size plays a role in developing a firm's operational activities (Ko et al, 2017) which in turn will increase the firm's performance. The result is consistent with the study of (Shyu, 2011;Ko et al, 2017;Ho and Mohd, 2019;Khan et al, 2019;Oyelade, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Besides that, an increase in a firm's size plays a role in developing a firm's operational activities (Ko et al, 2017) which in turn will increase the firm's performance. The result is consistent with the study of (Shyu, 2011;Ko et al, 2017;Ho and Mohd, 2019;Khan et al, 2019;Oyelade, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Firm performance is an interesting topic not only for academic scholars but also for policymakers, in which firm size is one of the main factors deciding the operation of any enterprises (Oyelade, 2019;Khemiri & Noubbigh, 2019). Majumdar (1997) showed that different sizes could affect the firm performance in various ways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firm size is among determinant factors of firm performance and particularly shows the profitability of business (Oyelade, 2019;Isik et al, 2017). In the context of international integration, emergence and vast influence of large enterprises-multinational corporations (MNCs) have proved the important role of scale in firm performance and business environment (Babalola, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…But Coad (2016) found that the age effects are occurred with the first 5-7 years. Finally, Oyelade (2019) examined that total sales and age of the firms have significant impact on the return on assets since the incorporation while the age of firm has a negative impact and total sales revenue has a positive impact.…”
Section: Literature Reviewmentioning
confidence: 99%